The Emotional Self-Efficacy Scale: Adaptation and Validation for Young Adolescents. (February 2015) - Qualter, P.; Pool, L. Dacre; Gardner, K. J.; Ashley-Kot, S.; Wise, A.; Wols, A.
Emotional self-efficacy (ESE) is an important aspect of emotional functioning, with current measures for children and adolescents focused on the measurement of self-beliefs in relation to the management of emotions. In the present study, we report the psychometric properties of the first adaptation of the Emotional Self-Efficacy Scale for youth (Youth-ESES) that measures additional aspects of ESE, such as perceiving and understanding emotions and helping others modulate their emotions. Participants were 192 young adolescents aged 11 to 13 years from a U.K. state school. They completed the Youth-ESES and measures of ability emotional intelligence (EI) and cognitive ability. Results support the same four-factor structure that has been previously documented using the adult version of the ESES, with the four subscales being largely independent from cognitive ability and only moderately related to ability EI. However, the four subscales were less differentiated in the present study compared with adult data previously published, suggesting that there is a strong general factor underlying young adolescents' ESE scores. Overall, the results suggest that the adapted Youth-ESES can be reliably used with youth, and that confidence in how a young person feels about his or her emotional functioning remains distinct from emotional skill.